PENGARUH KEPEMIMPINAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI MODAL SOSIAL. (STUDI PADA LINGKUNGAN ASISTEN ADMINISTRASI UMUM SEKDA KOTA SEMARANG) - Samsul Bahri Siregar, 11 42 02 0024 (Students Journal of Economic and Management, 2013)
The purpose of this study was to examine the effect of leadership and job characteristics on social capital and organizational commitment. The research was conducted in the General Administration Assistant Secretary of Semarang, respondents who used as many as 84 employees. The instruments used in this study is a questionnaire, the research instrument in this study has been qualified validity and reliability. Measurement validity with factor analysis showed all the indicator role in the research instruments have Loading Factor above 0.4 with a value of KMO sample adequacy or condition is above 0.5. Reliability tests of the variables studied has proven its reliability or konsistensiya, because it has a Cronbach alpha greater than 0.6. Technical analysis of data using multiple regression analysis. The results showed that leadership and job characteristics and significant positive effect on social capital, as well as the influence of leadership, job characteristics, and social capital and significant positive effect on organizational commitment. The results showed two equation model used for this study were eligible goodness of fi. The results of hypothesis testing showed that leadership and job characteristics positive effect on social capital and organizational commitment. Leadership has a dominant influence both the social capital and organizational commitment. Social capital was not a good influence mediating variable between leadership and job characteristics on employee performance, but the factor of social capital have tended to reinforce its influence on organizational commitment. Keywords: leadership, job characteristics, social capital and organizational commitment